Histórias em quadrinhos e educação infantil - ALVES, José Moysés (2016)
Different aspects of cartoon stories have attracted the attention of political scientists, sociologists, linguistics, and others. Psychologists and educators are interested in these stories because they affect the reader's education. The purpose of this study was to elucidate some relations between cartoon stories and childhood education, emphasizing the storie's context, their characteristics, and their educational value.